Venous flaps for coverage of traumatic soft tissue defects of the hand: a systematic review. (October 2017) - Wharton, R.; Creasy, H.; Bain, C.; James, M.; Fox, A.
A PRISMA-guided systematic review was performed of all published cases that detail the use of venous flaps for soft tissue reconstruction of the hand following trauma. Outcome measures examined included flap survival rates, venous congestion, and return to theatre. Database searches were performed on Medline, Embase, AHMED, CINAHL. A total of 381 articles were identified. Data were extracted from 45 articles that met inclusion criteria. A total of 756 flaps were described and their data analysed. A total of 75% of flaps were arterialized and 25% were pure venous flaps. There was no difference in survival rate for arterialized or pure venous flaps. Unplanned return to theatre occurred in 5.3% due to flap compromise or necrosis. Early venous congestion was present in 60% of cases. Total early failure requiring re-operation occurred in 19 flaps (2.5%) of cases. Venous flaps offer a versatile and well-tolerated reconstructive option. Early venous congestion is common, but can be managed non-operatively. Level of evidence: II